Trends and Correlates of Good Perinatal Outcomes in Assisted Reproductive Technology - Joshi, Nikhil (Obstet Gynecol, 2012)
OBJECTIVE: To estimate trends in good perinatal outcomes (singleton live births at term with birthweight more than 2,500 g) among live births after assisted reproductive technology in the United States from 2000 to 2008, and associated factors among singletons in 2008. METHODS: Using retrospective cohort data from the National Assisted Reproductive Technology Surveillance System from 2000 to 2008, we calculated relative change and χ(2) tests for trend in the proportion of good perinatal outcomes among assisted reproductive technology live births (n=444,909) and liveborn singletons (n=222,500). We conducted univariable analyses followed by multiple logistic regression to estimate the effects of various characteristics on the outcome among singletons born in 2008 after fresh, nondonor assisted reproductive technology cycles (n=20,780). RESULTS: The proportion of good perinatal outcomes among all liveborn neonates increased from 38.6% in 2000 to 42.5% in 2008, whereas it declined marginally among singletons from 83.6% to 83.4%. One previous birth, transfer of fewer than three embryos, and the presence of fewer than three fetal hearts on 6-week ultrasound examination were associated with good perinatal outcome among singletons. Non-Hispanic black race, tubal factor infertility, uterine factor infertility, ovulatory disorder, and 5-day embryo culture were associated with reduced odds for a good outcome. The strongest association was the presence of one fetal heart compared with more than two (adjusted odds ratio 2.43, 95% confidence interval 1.73–3.42). CONCLUSION: From 2000 to 2008, good perinatal outcomes increased among assisted reproductive technology live births. Among singleton live births, odds for good outcome were greatest with the presence of a single fetal heart and lowest in women of non-Hispanic black race. LEVEL OF EVIDENCE: II: